Analisis Omzet Penjualan Era Pandemi dan Pasca Pandemi Covid-19: Studi Kasus pada D’orbit Bistro, Lounge & KTV - Ardhiyah Regita Iriani; M.Ridwan Tikollah; Samirah Dunakhir (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to analyze the impact of the Covid-19 pandemic on the sales revenue of D'Orbit Bistro, Lounge & KTV and the strategies implemented for recovery during the period 2019-2022. During the pandemic, there was a drastic decrease in revenue by up to -64%, due to social restrictions and a decline in visitor interest. The outlet responded with CHSE strategies, discounts, and customer-centric approaches. Post-pandemic, there was an increase in revenue by 61%, with the implementation of entertainment, recruitment of new employees, and promotions on social media. The analysis of revenue changes provides a percentage overview of the decline and increase from the lowest point to the recovery of the outlet during the research period. This study offers insights into business adaptation and strategies amid significant environmental changes.